Fruiting-body-base flour from an oyster mushroom-a waste source of antioxidative flour for developing potential functional cookies and steamed-bun - Wan-Mohtar W.A.; Mahmud N.; Supramani S.; Ahmad R.; Zain N.A.M.; Hassan N.A.M.; Peryasamy J.; Halim-Lim S.A. (AIMS Press, 2024)
Indexed by WOS/SCOPUS